APPLICATION PERSPECTIVES OF THE ANTIINFLAMMATORY THERAPY IN TREATMENT OF THE LYMPHOPHARYNGEAL RING DISEASES AMONG CHILDREN IN OUTPATIENT PRACTICE - V.P. Vavilova; O.A. Vaiman; T.Yu. Milkova ("Paediatrician" Publishers LLC, 2008)
Optimization of methods to treat and rehabilitate children, suffering from lymphopharyngeal ring diseases, is an urgent medical and social issue. The purpose of the given research was to study the efficacy of fenspiride (erespal) in treatment of children with chronic lymphopharyngeal ring diseases. The authors generalized the findings of the 3byear dynamic observation carried out among 157 children aged between 3 and 8 years old. They found out that the 2B week fenspirideb based therapy in average age doses has positive effects on the run of the acute respiratory infection, coming to existence against the hypertrophy of the lymphopharyngeal ring tissues, accelerates the remission of chronic adenoiditis. In the event of the repeat application, fenspiride increases efficacy of the nonspecific resistance and local immunity factors, rebuilds the microflora, slows down the progress of hypertrophy of the lymphopharyngeal ring tissues. Thus, fenspiridebbased therapy is a perspective trend in treatment of children with chronic lymphopharyngeal ring diseases. Key words: children, fenspiride, lymphopharyngeal ring diseases.